A User-centered Decision-aiding Process for Selecting Power Analysis Tools. (December 2020) - Hung, Ya-Hsin; Choi, Jeong Yun; Willis, Mairéad; Proctor, Robert W.; Hennes, Erin P.; Lane, Sean P.
A priori power analyses have become increasingly popular in scientific communities, but the practice has not been widely discussed by HFE researchers. Given the complexity of conducting such analyses, software tools are essential. We review the emergence and current state of power analysis software tools, and use the concept of User-Centered Design as an analytical lens for examining the relationship between researchers' needs and power analysis tools' characteristics. Centering on users' wants and needs, we propose a decision-aiding process to assist researchers in identifying appropriate power analysis tools. This process consists of five user-centered considerations – two functional criteria (software input; software output) and three usability heuristics (learnability; ease of use; accessibility) – which are organized into a workflow. These criteria and heuristics are translated into questions that researchers should go through during the decision process. We illustrate use of the decision-aiding process with three example scenarios and lay out implications for researchers.